2019
DOI: 10.4081/or.2019.7963
|View full text |Cite
|
Sign up to set email alerts
|

Single versus separate implant fixation for concomitant ipsilateral femoral neck and shaft fractures: A systematic review

Abstract: Concomitant ipsilateral femoral neck and shaft fractures are uncommon, occurring in 1-9% of femoral shaft fractures. While this injury typically occurs in young patients following high-energy trauma, little consensus has been established regarding the optimal fixation approach. A multitude of treatment strategies exist, with limited evidence as to which is more favorable. The aim of this study was to appraise current evidence, comparing management with either one single or separate devices for both fractures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Boulton et al in a 2014 systematic review, indicated their preference for a dual implant, femoral neck fracture first approach [ 5 ]. A more recent systematic review, found favorable outcomes in both treatment groups, and called for prospective, randomized trials to definitively guide treatment strategy [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Boulton et al in a 2014 systematic review, indicated their preference for a dual implant, femoral neck fracture first approach [ 5 ]. A more recent systematic review, found favorable outcomes in both treatment groups, and called for prospective, randomized trials to definitively guide treatment strategy [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…We chose a dual construct, stabilizing the femoral shaft fracture first with a RFN and then using a DHS in an overlapping configuration, to treat the femoral neck fracture, the so-called “rendezvous” technique [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concomitant ipsilateral femoral shaft and neck fractures usually result from high-velocity injuries in young patients [1][2][3]. The incidence of these injuries is approximately 1% to 9% of all femoral shaft fractures [4,5]. In polytraumatized patients, these injuries are often missed and delayed diagnoses are common as the femoral neck fracture pattern is either undisplaced or minimally displaced.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, due to the inherent instability of this fracture pattern, the fixation may fail prior to the achievement of fracture union. Infected nonunion of fracture is another entity that frequently complicates the fracture healing process [ 2 ]. The management of infected fracture nonunions has never been simple, and often requires staged management in the form of infection control measures followed by the definitive fixation.…”
Section: Introductionmentioning
confidence: 99%